Novel high-entropy alloys with high-density ε-D019 and abnormal phase transformation. (1st July 2021) - Xia, G.H.; Ma, Z.L.; Xu, Z.Q.; Wang, M.; Cheng, X.W.; Cai, H.N.
Abstract: Precipitation strengthening is considered to be one of the most effective ways to improve engineering structural materials. However, introducing high-density nanoprecipitates in alloys is a big challenge. In this study, novel CoFeNiVTa(Nb) high-entropy alloys (HEAs) with high-density ε-D019 nanoprecipitates featuring Widmanstätten patterns and coherent interfaces with the matrix are developed using the lattice misfit design concept. The highly ordered hexagonal ε-D019 phase is identified as (Co, Ni, Fe)3 (V, Nb, Ta, Fe) by atomic resolution energy dispersive spectrometry and this phase is metastable and can be abnormally transformed into δ-D0a phase instead of η-D024 . The superior thermodynamic stability of the δ phase compared with the ε phase is confirmed by first-principle calculations. High-density ε-D019 precipitates with Widmanstätten patterns contribute to the improved strengthens and friction properties of CoFeNiVTa(Nb) HEAs. Graphical abstract: Image, graphical abstract